Mandibular fractures at a tertiary health care facility: a pilot study - Munjal, Manish; Kanotra, Sonika; Munjal, Shubham; Chopra, Parth; Saggar, Tulika; Bharadwaj, Iti; Chopra, Hemant; Uppal, Sanjeev (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Facial trauma patients were analyzed to determine the incidence, type, presentation, management, and outcome of fractures of the mandible. Methods: The 61 patients admitted in the trauma units of Dayanand medical college Ludhiana were analyzed prospectively during a period of two years (January 2010-December 2012). Results: In patients with multiple fractures, the common combination included zygoma and mandible (35.2%) and Le Fort II, mandible and nasoethmoid (41.2%). Out of 35 patients with mandible fractures, 8 had bilateral and 27 had single fractures making a total of 43 fractures. The body of mandible. 46.5% followed by the angle 34.8%, symphysis 9.3%, and parasymphysis 4.6% ramus and condoyle in 2.3% each were seen. Of the single mandibular fractures, the body and angle were almost equally affected in 48% and 44% cases, respectively. Isolated fracture of symphysis and parasymphysis was seen in 3.7% cases each. Isolated fracture of the ramus or condyle was not seen in any case. Half of the angle fractures were treated by wiring while shown in 1/4th each, plating and external fixation was used for treatment. Almost half (6/13) of fractures of the body were treated with external fixation. All bilateral fractures were treated with bone plating. Conclusions: Road traffic accidents are the major cause of these fractures. Mandibular fractures are commonly associated with fractures of other facial bones. The fracture line commonly seen is in the body of mandible, followed by the angle.